The effect of eating alone and eating with familiar or unfamiliar others on food intake: A systematic review - Mohamed Nor, Noraishah; Mohd Nasir, Nurul Khaleda; Mohd Shukri, Nor Azwani (Faculty of Medicine and Health Sciences, UPM, 2023)
Aims and Design: Individuals' food intake may vary depending on their situation and with whom they are having their meal. Thus this systematic review aimed to compare the effect of social facilitation between eating alone and eating with others, and evaluate the social modeling effect when eating with familiar or unfamiliar others, on food intake. Data Sources: Articles were screened and reviewed based on titles, abstracts and keywords. Inclusion criteria included experimental design, English language, open-accessed, and published from 1980 until the review was conducted in 2018. Review Methods: Using the PRISMA method, potential studies were identified on Science Direct, ProQuest, PubMed, Scopus, and BASE databases using two different keywords combinations. Results: Seventeen studies were included. For social facilitation, seven studies found that food intake increases when eating alone while five others stated it would increase when eating with others. One study suggested that it increases in both situations. For social modeling of food intake, two studies found that it commonly occurs when an individual eats in the presence of unfamiliar others, while one study reported that it happens more often with familiar others. Two other studies observed that social modeling occurs in both situations. Conclusion and Impact: Food intake tends to increase when eating alone than eating with others while the presence of familiar or unfamiliar others may either increase or limit an individual’s food consumption to socially match their co-eaters’ intake. Thus, good self-control is crucial for setting a dietary limit regardless of whether ones are eating alone or with familiar or unfamiliar others.